1998
DOI: 10.2516/ogst:1998061
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Seismic Anisotropy Revisited

Abstract: Un principe gŽnŽral esquissŽ par P. Curie (1894) concernant lÕinfluence de la symŽtrie sur les phŽnom•nes physiques dit, en langage actuel, que le groupe de symŽtrie des causes est un sousgroupe du groupe de symŽtrie des effets. Par exemple, en ce qui concerne lÕanisotropie sismique induite par les contraintes, la symŽtrie la plus complexe prŽsentŽe par un milieu initialement isotrope, sous contrainte triaxiale, est orthorhombique ou orthotrope, caractŽrisŽe par trois plans de symŽtrie orthogonaux deux ˆ deux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
37
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 22 publications
12
37
0
1
Order By: Relevance
“…The result concerning the ellipticity of stress-induced anisotropy is consistent with a theoretically proven fact: elastic anisotropy arising from the application of anisotropic stress to an elastic medium that can be described by isotropic third-order elasticity (so that both second-and third-order elasticity tensors are isotropic) is always elliptical (see Rasolofosaon, 1998;Fuck and Tsvankin, 2009). Our model is a particular case of isotropic third-order elasticity.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The result concerning the ellipticity of stress-induced anisotropy is consistent with a theoretically proven fact: elastic anisotropy arising from the application of anisotropic stress to an elastic medium that can be described by isotropic third-order elasticity (so that both second-and third-order elasticity tensors are isotropic) is always elliptical (see Rasolofosaon, 1998;Fuck and Tsvankin, 2009). Our model is a particular case of isotropic third-order elasticity.…”
Section: Discussionsupporting
confidence: 88%
“…We will now assume that normal stresses are small compared to P c . This assumption is equivalent to the assumption of third-order elasticity (Rasolofosaon, 1998;Prioul et al, 2004;Fuck and Tsvankin, 2009) and results in linear variation of elastic compliances with stress. With this assumption, the exponential expression in Equation 5 can be approximated by a linear expression…”
Section: Effect Of Stress On Crack Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rasolofosaon [12] showed that application of anisotropic stress to an isotropic drained rock results in ellipsoidal anisotropy. The stretched HTI porous medium in this case results in elliptical anisotropy, meaning that for drained rock Thomsen's anisotropy parameters ε and δ are equal, which is equivalent to 1 r  or N T Z Z  .…”
Section: The Main Assumption and Its Justificationmentioning
confidence: 99%
“…e is used to measure the anisotropic intensity of P wave, which reflects the difference between the horizontal phase velocity and vertical phase velocity of P wave, whereas d is a transitional parameter associated with vertical phase velocity and horizontal phase velocity of P wave, reflecting the magnitude of anisotropy of phase velocity near the vertical direction of P wave (Niu et al 2002). Rasolofosaon (1998) suggested that the anisotropy induced by stress may be elliptical anisotropy. Therefore, the elliptically anisotropic media is common in the ground which is the anisotropic media with the least parameters observed so far (Gurvich 1940;Kleyn 1956;Levin 1978;Daley and Hron 1979;Rogister and Slawinski 2005;Grechka 2009).…”
Section: Elliptically Anisotropic Mediamentioning
confidence: 99%